The Influence of Immunological Factors in the Development of Congenital Heart Defects (Literature Review) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The development of CHD is a complex and multifactorial process that genetic factors can interact with other environmental factors such as environmental, epigenetic and behavioral factors. The review provides an analysis of current ideas about the role of immunogenetic factors in the development of CHD and mechanisms for developing approaches to the prevention and treatment of these heart defects in children.